2017
DOI: 10.3389/fnmol.2017.00135
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Translation: Defects in Transfer RNA Modifications and Neurological Disorders

Abstract: Transfer RNAs (tRNAs) are key molecules participating in protein synthesis. To augment their functionality they undergo extensive post-transcriptional modifications and, as such, are subject to regulation at multiple levels including transcription, transcript processing, localization and ribonucleoside base modification. Post-transcriptional enzyme-catalyzed modification of tRNA occurs at a number of base and sugar positions and influences specific anticodon–codon interactions and regulates translation, its ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 88 publications
0
36
0
Order By: Relevance
“…In this regard, several RNA methyltransferase-encoding genes have been linked to intellectual disability, supporting the relevance of RNA modifications in the development of cognitive functions (Bednárǒvá et al 2017). These include FTSJ1, identified in X-linked nonsyndromic intellectual disability in which mental retardation is the sole clinical feature (Freude et al 2004); TRMT1, which has been identified as the cause of autosomalrecessive intellectual disability (ARID) (Najmabadi et al 2011;Davarniya et al 2015); and the m 5 C methyltransferase NSUN2, which has been associated with defects in memory and learning in Drosophila and NSUN2-deficient mouse models (Abbasi-Moheb et al 2012;Blanco et al 2014).…”
Section: Neurological Diseasesmentioning
confidence: 85%
“…In this regard, several RNA methyltransferase-encoding genes have been linked to intellectual disability, supporting the relevance of RNA modifications in the development of cognitive functions (Bednárǒvá et al 2017). These include FTSJ1, identified in X-linked nonsyndromic intellectual disability in which mental retardation is the sole clinical feature (Freude et al 2004); TRMT1, which has been identified as the cause of autosomalrecessive intellectual disability (ARID) (Najmabadi et al 2011;Davarniya et al 2015); and the m 5 C methyltransferase NSUN2, which has been associated with defects in memory and learning in Drosophila and NSUN2-deficient mouse models (Abbasi-Moheb et al 2012;Blanco et al 2014).…”
Section: Neurological Diseasesmentioning
confidence: 85%
“…A new frontier in understanding the details of the central dogma of biology involves the effects of posttranscriptional tRNA modifications, some of which may be nearly universal across phyla while others are phylum specific (23). More than 100 such tRNA modifications have been identified, a major fraction in their RNA anticodon loops (24). Modifications include deamination of adenosine to inosine, introduction of the modified nucleoside, queuosine, thiolation, methylation, isopentenylation, 5-methoxycarbonyl methylation, threonyl carbamoylation, and others (25)(26)(27)(28).…”
Section: Dependency Of Translation On Trna Modificationsmentioning
confidence: 99%
“…While there are several conserved locations for tRNA modifications within 70–90 nucleotides long tRNAs, specific modification at the anticodon loop is vital to reprogram translation under stress . According to their importance, perturbations in tRNA modifications are broadly associated with multiple human pathologies (discussed in Zhang and co‐workers).…”
Section: Reprogramming Of Protein Synthesis Under Stressmentioning
confidence: 99%
“…reprogram translation under stress. [61] According to their importance, perturbations in tRNA modifications are broadly associated with multiple human pathologies (discussed in Zhang and co-workers [62][63][64] ). The modification at the wobble base greatly alters the kinetics of the codon:anticodon interactions, thereby altering the codon dependent stability and expression of specific transcripts.…”
Section: Dynamic Trna Modifications Fine-tune Translation Under Stressmentioning
confidence: 99%